The Ahl al-Sunnah wa al-Jama’ah in Southeast Asia: The Literature of Malay-Indonesia ‘Ulama’ and Reforms - Azyumardi Azra (Center for Research and Development of Religious Literature and Heritage, 2013)
Muslims in Southeast Asia are overwhelmingly dominant by group of Ahl al-Sunnah wa al-Jamaah (Aswaja), the so-called Sunni. They contributed a great deal to the formation of distinct Islamic tradition that can stillibe observed today. In Indonesia, the history of the Aswaja can be considered as the continuous consolidation of orthodoxy which appeared through some successive reforms and santrinization. This consolidation has, of course, played important role for strengthening Malay-Indonesian ulama relationship. This study focusses on the literature used by Malay-Indonesian ulama and reforms performing their idea to their society. This study argues that the Malay-Indonesian ulama were mostly responsible for earliest reforms of Islamic teaching an Muslim life in the archipelago.